PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG DAMPAK PERNIKAHAN DINI PADA KESEHATAN MENTAL DAN FISIK - Munawir, Ahmad; Handayani, Rini Sri; Angelina, Riyanti; Azzahra , Naila Kamila; Mulyatiningsih, Yuni (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Marriage is a spiritual and legal union between a man and a woman to form a family and have offspring. Early marriage has become an increasing phenomenon, yet it causes serious issues due to its negative impact on youth development. These impacts include psychological, social, health, household resilience, and economic aspects. This community service aims to raise awareness among the community and adolescents about the dangers of early marriage using lectures, discussions, and question-and-answer sessions. Participants consisted of community members and active students in Cimanis Village, Sobang Subdistrict, Pandeglang Regency, Banten Province. The results showed active participation in discussions, the ability to answer questions, and improved understanding of the importance of education, legal marriage age, and the negative consequences of underage marriage. This program is expected to increase awareness among the community and adolescents to postpone marriage to the appropriate age, thereby supporting mental and physical health as well as sustainable family well-being.